Obraz pandemii w polskich i rosyjskich połączeniach wyrazowych - Kuligowska, Katarzyna (Studia Rossica Posnaniensia, 2023)
Since the beginning of 2020, the Covid-19 pandemic has changed not only many aspects of everyday life, but also the lexical systems of languages. Polish and Russian have been enriched with numerous derivatives, loan words, as well as new collocations pretending to become neophrasemes. The linguistic image of the pandemic consists of miscellaneous metaphorical expressions picturing the reality in terms of war, sports’ competitions or natural disasters. New Polish and Russian collocations present different problems of the pandemic crisis and the diverse attitude of individuals and social groups to its threat to public health and the measures taken by governments and international institutions. Furthermore, the analyzed pandemic discourse contains many examples of intertextuality sensu lato. These are allusions to literary texts, music, film, and history. The image of the pandemic in Polish and Russian has been complemented by means of idiomatic transformations, humorous expressions and jokes, which are natural and spontaneous answers to long-lasting fear, anxiety and frustration.